P143 Using big data to investigate physiology: retention of co2 does not impact the oxygen-haemoglobin dissociation curve of critically ill adults. (15th November 2017) - Rosculet, N; Samata, R; Dixit, A; Harris, S; MacCallum, NS; Brearley, DA; Watkinson, PJ; Jones, A; Ashworth, S; Beale, R; Brett, SJ; Young, JD; et al.
Abstract : Introduction: Since its initial description in 1904, the oxygen-haemoglobin dissociation curve (ODC) has been well described under physiological conditions. 1, 2 However, the impact of pathology has been less well characterised, with most data arising from small clinical studies of anaesthetized adults/patients (<100 subjects), or experimentally-induced hypoxaemia/hypercapnia. Routinely collected clinical data, including arterial blood gas analyses, are now available from many thousands of critically ill patients. We sought to investigate the impact of pCO2 on the ODC of critically ill adults, and hypothesised that pCO2 would not significantly alter the relationship between pO2 and haemoglobin saturation. Methods: Data was extracted from the National Institute for Health Research Critical Care Health Informatics Collaborative (NIHR ccHIC). Statistical analysis was undertaken on 3 99 000 blood gases from 13 942 patients, using R version 3.4.0. After data cleaning, the predicted oxygen saturation for each arterial blood gas sample was calculated using both the Severinghaus 1 and Dash, Kroman and Bassingthwaighte 2 equations. Non-linear regression modelling was undertaken to construct ODCs based on both the predicted and observed data, to allow comparison. Observed data was stratified into strata based on pCO2 to investigate the influence of hypercapnia on the ODC. Results: No clinically significant impact of pCO2 on the relationship between pO2 and oxygen saturation was observed in samples obtained from critically ill adults (mean difference 0.35 kPa (SD=0.2 kPa) for a given oxygen saturation). Interestingly, we did not observe "right shift" of the ODC in response to elevated arterial pCO2, and there was no impact of either acute (HCO3 <28 mmol/L) or chronic (HCO3 ≥28 mmol/L) hypercapnia on the relationship between haemoglobin saturation and pO2. Conclusions: These data suggest that the relationship between haemoglobin saturation and pO2 described by data from small scale studies may not reflect physiology observed in critically ill adults, and further that the right shift of the ODC reported in experimental hypercapnia, induced in healthy subjects, is not reproduced in the critically ill. References: Severinghaus JW. J Appl Physiol Respir Environ Exerc Physiol 1979;46:599. Dash RK, Kroman B, Baasingthwaighte JB. Eur J Appl Physiol2016;116:97.